PENYUSUNAN BAHAN AJAR DENGAN PENGINTEGRASIAN KOMPETENSI LISTENING DAN SPEAKING BAGI MAHASISWA PBI - Nurhayati, Lusi; Diyanti, B. Yuniar; Kurniasih, Siwi Karmadi (Diksi, 2019)
(Title: Development of Teaching Materials By Integrating Listening and Speaking Competency For PBI Students). This study aims to produce teaching material models by integrating listening and speaking competencies. This research is a type of research and development (Research and Development). The research subjects were 5th semester students who had taken the Listening for Academic Purposes and Speaking for Academic Purposes courses. The integration of learning material in the Listening for Academic Purposes (LAP) and Speaking for Academic Purposes (SAP) courses for PBI students in semester 4 is very necessary. The steps that have been carried out in this study have reached the stage of needs analysis and have succeeded in identifying several important things needed in developing teaching materials such as types of texts, activities needed and liked by students, types of media that can be used, reaction patterns and assessments . The learning material in the LAP course is prioritized on providing exposure to prepare students to be able to produce appropriate speeches and expressions in the SAP class. Keyword: bahan ajar, listening, speaking, academic purposes